Pengembangan Keterampilan Santri melalui Pelatihan Desain Grafis di Syarif Hidayatullah Cyber Pesantren - Nurus Sariroh Al Hasanah; Moh Zainal Fanani (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
Pesantren is a place to learn about religious knowledge, in the modern era students not only master religious knowledge but other skills must be mastered such as graphic design. These skills and abilities will be needed by students in the future, therefore one solution in helping these problems is the holding of graphic design training aimed at new students of Syarif Hidayatullah Cyber ​​Islamic Boarding School. The graphic design training activities carried out were focused on twibbon design training using Corel Draw X7. The implementation stage is the delivery of material, practice, and the last evaluation. The results achieved during the training can be seen from the enthusiasm of the students in participating in the training.